2020 8th International Workshop on Biometrics and Forensics (IWBF) 2020
DOI: 10.1109/iwbf49977.2020.9107970
|View full text |Cite
|
Sign up to set email alerts
|

Can GAN Generated Morphs Threaten Face Recognition Systems Equally as Landmark Based Morphs? - Vulnerability and Detection

Abstract: The primary objective of face morphing is to combine face images of different data subjects (e.g. a malicious actor and an accomplice) to generate a face image that can be equally verified for both contributing data subjects. In this paper, we propose a new framework for generating face morphs using a newer Generative Adversarial Network (GAN)-StyleGAN. In contrast to earlier works, we generate realistic morphs of both high-quality and high resolution of 1024×1024 pixels. With the newly created morphing datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 17 publications
1
91
0
Order By: Relevance
“…Recent improvements in deep learning-based techniques have given rise to morph generation approaches based on generative adversarial networks (GANs) [41] [125]. In general, GAN-based methods synthesise morphed images that are generated by sampling two facial images in the latent space of the deep learning network.…”
Section: B Deep Learning-based Morph Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent improvements in deep learning-based techniques have given rise to morph generation approaches based on generative adversarial networks (GANs) [41] [125]. In general, GAN-based methods synthesise morphed images that are generated by sampling two facial images in the latent space of the deep learning network.…”
Section: B Deep Learning-based Morph Generationmentioning
confidence: 99%
“…The generator is trained to generate images with dimensions of 64 × 64 pixels. Another recent approach based on StyleGAN architecture [24], [125] has improved the morph generation process both by increasing the spatial size to 1024×1024 and by increasing face quality. The pre-trained StyleGAN achieves this by embedding the images in the intermediate latent space.…”
Section: B Deep Learning-based Morph Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we plan to extend this framework such that it can be used without having a reference image. Without having to rely on a reference image, we would also be able to use the framework for morphed face images generated by Generative Adversarial Networks [29].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The generator was trained to generate images with the dimension 64 × 64 pixels which is a key limiting factor of the attack, as most commercial FRS will reject images that do not meet the ICAO standard that requires a minimum Inter-Eye Distance (IED) of 90 pixels. The empirical evaluation of generated morph images using MorGAN in a vulnerability analysis against two commercial FRS indicated that those MorGAN morphs fail to meet both quality standards and the verification threshold of the FRS [1]. Motivated to address the deficiency of the MorGAN architecture, in our recent work [1] 1 we proposed an approach based on the StyleGAN architecture [29] to increase the spatial dimension to 1024 × 1024 and thus to improve the face image quality.…”
Section: Gan Based Face Morph Generationmentioning
confidence: 99%